Analisis Laporan Keuangan Untuk Menilai Kinerja Keuangan Pada Bank Umum Syariah Di Indonesia Periode 2012-2014 (Studi Kasus Bank Muamalat Indonesia, Bank Syariah Mandiri, dan Bank Negara Indonesia Syariah) - Khotimah, Nurul, Dra.Wuryaningsih DL, M.M (2016)
This study aimed to analyze the financial performance of the Indonesian Islamic Banks in the period 2012-2014 in terms of the ratio of liquidity, solvency, profitability and efficiency. The results of this study are expected to provide information about the financial position of the company for consideration in making policy and strategy of the company in improving its financial performance. Secondary data sources used by the writer of this form of financial statements that have been issued by Bank Muamalat Indonesia, Bank Syariah Mandiri and Bank Negara Indonesia Syariah during the period 2012-2014 were obtained from the Internet by downloading financial statements via the website http: /// www. bi.go.id. Analysis of the data used is the analysis of financial ratios of the liquidity ratio, solvency, profitability and efficiency ratios. Based on this research, it is known that the liquidity ratio analysis showed that in the year 2012-2014 Islamic Banks in Indonesia have included the category of healthy performance by banking ratio and loan to assets ratio, but based on the quick ratio is not good. The results of the analysis of the solvency ratio at the Islamic Banks in Indonesia during the period 2012-2014 as measured by the primary ratio, capital ratio and capital adequacy ratio is known that during the years 2012-2014 are included in the category of bad (unhealthy), the results of the calculation of the ratio Bank profitability in general Sharia in Indonesia is known that during the years 2012-2014 was measured by return on assets in the unfavorable category, while based on return on equity and a gross profit margin of Islamic Banks in Indonesia during the period 2012-2014 included in the excellent category. Based on the calculation on the level of cost efficiency in Islamic Banks in Indonesia is known that during the period 2012-2014 the value of the cost efficiency of banks included in either category.